Filling two needs with one deed: a combinatory mucosal vaccine against influenza A virus and respiratory syncytial virus - Vieira Antao, Ana Isabel; Oltmanns, Friederike; Schmidt, Anna; Viherlehto, Vera; Irrgang, Pascal; Rameix-Welti, Marie-Anne; Bayer, Wibke; Lapuente, Dennis; Tenbusch, Matthias (Frontiers in Immunology, 2024)
Influenza A Virus (IAV) and Respiratory Syncytial Virus (RSV) are both responsible for millions of severe respiratory tract infections every year worldwide. Effective vaccines able to prevent transmission and severe disease, are important measures to reduce the burden for the global health system. Despite the strong systemic immune responses induced upon current parental immunizations, this vaccination strategy fails to promote a robust mucosal immune response. Here, we investigated the immunogenicity and efficacy of a mucosal adenoviral vector vaccine to tackle both pathogens simultaneously at their entry site. For this purpose, BALB/c mice were immunized intranasally with adenoviral vectors (Ad) encoding the influenza-derived proteins, hemagglutinin (HA) and nucleoprotein (NP), in combination with an Ad encoding for the RSV fusion (F) protein. The mucosal combinatory vaccine induced neutralizing antibodies as well as local IgA responses against both viruses. Moreover, the vaccine elicited pulmonary CD8+ and CD4+ tissue resident memory T cells (TRM) against the immunodominant epitopes of RSV-F and IAV-NP. Furthermore, the addition of Ad-TGFβ or Ad-CCL17 as mucosal adjuvant enhanced the formation of functional CD8+ TRM responses against the conserved IAV-NP. Consequently, the combinatory vaccine not only provided protection against subsequent infections with RSV, but also against heterosubtypic challenges with pH1N1 or H3N2 strains. In conclusion, we present here a potent combinatory vaccine for mucosal applications, which provides protection against two of the most relevant respiratory viruses.
CRIS-Team Scopus Importer:2024-07-12
Keywords: adjuvant; combinatory vaccine; influenza A virus (IAV); mucosal immunity; respiratory syncytial virus (RSV); respiratory viruses

Inflammatory conditions shape phenotypic and functional characteristics of lung-resident memory T cells in mice - Schmidt, Anna; Fuchs, Jana; Dedden, Mark; Kocher, Katharina; Schülein, Christine; Hübner, Julian; Vieira Antao, Ana Isabel; Irrgang, Pascal; Oltmanns, Friederike; Viherlehto, Vera; Leicht, Natascha; Rieker, Ralf; et al. (Nature Communications, 2025)
Lung tissue-resident memory T cells (TRM) are critical for the local control of respiratory tract infections caused by influenza A viruses (IAV). Here we compare TRM populations induced by intranasal adenoviral vector vaccines encoding hemagglutinin and nucleoprotein (NP) with those induced by an H1N1 infection in BALB/c mice. While vaccine-induced TRM express high levels of CD103 and persist longer in the lung parenchyma, short-lived, H1N1-induced TRM have a transcriptome associated with higher cytotoxic potential and distinct transcriptional profile as shown by single-cell RNA sequencing. In both the vaccine and H1N1 groups, NP-specific CD8+ T cells expand during heterologous influenza virus infection and protect the mice from disease. Meanwhile, lung inflammation in response to an infection with unrelated respiratory syncytial virus do not influence the fate of pre-existing TRM. Our preclinical work thus confirms that inflammatory conditions in the tissue shape the phenotypic and functional characteristics of TRM to serve relevant informations for optimizing mucosal vaccines.
CRIS-Team Scopus Importer:2025-05-02

Mucosal tumor vaccination delivering endogenous tumor antigens protects against pulmonary breast cancer metastases - Oltmanns, Friederike; Vieira Antao, Ana Isabel; Irrgang, Pascal; Viherlehto, Vera; Jörg, Leticia; Schmidt, Anna; Wagner, Jannik; Rückert, Michael; Flohr, Ann-Sophie; Geppert, Carol-Immanuel; Frey, Benjamin; Bayer, Wibke; et al. (Journal for ImmunoTherapy of Cancer, 2024)
Background Generally, early-stage breast cancer has a good prognosis. However, if it spreads systemically, especially with pulmonary involvement, prospects worsen dramatically. Importantly, tumor-infiltrating T cells contribute to tumor control, particularly intratumoral T cells with a tissue-resident memory phenotype are associated with an improved clinical outcome. Methods Here, we use an adenoviral vector vaccine encoding endogenous tumor-associated antigens adjuvanted with interleukin-1β to induce tumor-specific tissue-resident memory T cells (TRM) in the lung for the prevention and treatment of pulmonary metastases in the murine 4T1 breast cancer model. Results The mucosal delivery of the vaccine was highly efficient in establishing tumor-specific TRM in the lung. Concomitantly, a single mucosal vaccination reduced the growth of pulmonary metastases and improved the survival in a prophylactic treatment. Vaccine-induced TRM contributed to these protective effects. In a therapeutic setting, the vaccination induced a pronounced T cell infiltration into metastases but resulted in only a minor restriction of the disease progression. However, in combination with stereotactic radiotherapy, the vaccine increased the survival time and rate of tumor-bearing mice. Conclusion In summary, our study demonstrates that mucosal vaccination is a promising strategy to harness the power of antitumor TRM and its potential combination with state-of-the-art treatments.
CRIS-Team Scopus Importer:2024-03-22